Strategic Marketing - David W. Cravens (Boston: Irwin, 1991)
The book is designed around a strategic marketing planning approach with a clear emphasis on how to do strategic analysis and planning. The text is divided into five parts.
(NP(B/3042-(NP(B/3051s
Keywords: business strategy -- marketing strategy -- price strategy